Analisis Kelayakan Usaha Tahu Mandiri Desa Kotangan Kecamatan Galang Kabupaten Deli Serdang - Muhammad Deaprama Aydra; Retna Astuti Kuswardani; Mitra Musika Lubis (Jurnal Ilmiah Pertanian ( JIPERTA), 2020)
The purpose of this study is to analyze the feasibility of the financial and non-financial aspects of Mandiri tofu business. Data analysis methods used are qualitative (legal, environmental, market and marketing, technical and management and human resource aspects) and quantitative to analyze financial aspects through four investment criteria, namely NPV, IRR, Net B / C, payback period. Non-financial aspects of the legal aspect are unfeasible because the Business Ownership Permit only has a Letter of Submission of Land Tenure by Compensation. The management aspect isn’t feasible because this business doesn’t yet have a good financial record and doesn’t have an organizational structure. Environmental aspects aren’t feasible because it discharges its wastewater directly to the nearest river without special treatment. The financial analysis used NPV value obtained at Rp 109,897,985, Net B / C at 2.02, IRR at 49.26%, and payback period for three years and ten months eleven days on the first investment and NPV value obtained at Rp 66,127,532, Net B / C is 1.25, IRR is 34.06%, and the payback period is two years ten months and thirteen days on the second investment. Financial and non-financial aspects state Mandiri tofu business is feasible to except in legal, management, and environmental aspects.